PENGGUNAAN LEGAL STANDING ORGANISASI LINGKUNGAN HIDUP DALAM RANGKA PENEGAKAN HUKUM LINGKUNGAN - Fajar Winarni (Fakultas Hukum Universitas Gadjah Mada, 2008)
The research results show that the implementation of the WALHI legal standing is only implemented in two cases. They are Taman Nasional Gunung Merapi and PT. Griya Perwita Asri case. The efforts of the law enforcement that have been conducted by WALHI tend to the advocacy and the awareness of the community rights toward environmental. Meanwhile, the obstacles which are faced by WALHI in implementing its legal standing are WALHI is tends to do the awareness of the community rights and advocacy than legal standing, because it is most appropriate target; the law officers are lack response to the legal standing case; the regulation is not clear yet; and the lack of the human resources. Although the implementation of the WALHI legal standing is not effective yet, but their roles in criticizing the Government policy have been giving a lot of changes through the pressures that have been done.